Software Geogebra na exploração de geometria fractal por meio da modelagem matemática - LOBO, Rafaeli Pereira (2022)
This work presentes na experience report regarding the pedagogical practice activity developed with third year high school students. In order to analyze the sbsidies that Mathematical Modeling through Geogebra software enables in the optmization of the teaching of mathematicl contentes involved in Fractal GEometry. For the study, a qualitative research was developed, whose data were produced from modeling activities developed around Geogebra fractal construtions, such as Koch curve, Sierpinski triangle and others. The actions performed thought the use of Mathematical Modeling with the use of Geogebra software provided connections with mathematical contentes, creating means for the improvement of knowledge, constituing na interconnected process between Fractal constructions performed in Geogebra and Mathematical contentes mediated or acquired by Geogebra means of Mathematical Modeling.